SPSS for dummies - Griffith, Arthur (Hoboken, N.J. ; Chichester : John Wiley, 2010)
Need to analyze some data? SPSS is your statistical friend-- let it crunch the numbers!
pt. I. The fundamental mechanics of SPSS. Introducing IBM SPSS statistics ; Installing software and setting options ; A simple statistical analysis example -- pt. II. Getting data in and out of SPSS. Entering data from the keyboard ; Reading and writing files ; Data and data types ; Messing with the data after it's in there ; Getting data out of SPSS -- pt. III. Graphing data. Fundamentals of graphing ; Some types of graphs ; More types of graphs -- pt. IV. Analysis. Executing an analysis ; Some analysis examples -- pt. V. Programming SPSS with command syntax. The command syntax language ; Command syntax language example -- pt. VI. Programming SPSS with Python and Scripts. the Python programming language ; Python inside SPSS ; Scripts -- pt. VII. The part of tens. Ten (or so) modules you can add to SPSS ; Ten useful SPSS things you can find on the Internet.
Includes index.
Keywords: SPSS (Computer file); PASW (Computer file); Social sciences -- Statistical methods -- Computer programs